Family planning requires special attention as strategy to reduce maternal mortality - Tavara, Luis (2015)
Objectives: To socialize and discuss recent investigations on the current status of family planning services and their relationship with maternal mortality figures in order to reach consensus on a guide proposed for use in the public sector. Methods: Three Regional Forums were organized with participation of a group of experts at national level and a group of experts at each of the three regions involved in the intervention (Arequipa, Piura y Ucayali). Consensus on thematic content and event development methodology was obtained. Contents centered on: Sexual and Reproductive Rights review, ENDES 2010 Survey results, maternal mortality figures recently processed by the Epidemiology General Direction of the Ministry of Health, evaluation of maternal mortality, family planning and Compromise Round Table for Fighting Poverty at regional level. Contents were exposed by experts followed by a space for questions, answers, opinions, comments and criticism, contributions and proposals. Results: There was ample participation of representatives of various institutions that led to acknowledging evident advances in sexual and reproductive health, particularly in prenatal care, institutional delivery care and other obstetrical interventions that have permitted Maternal Death Rate reduction in the last 10 years. Nevertheless there are gaps to get over in obstetrical care in vulnerable groups and in family planning activities as fecundity has not decreased according to women’s wish, adolescent girls continue getting pregnant at high figures, there is an important number of unwanted pregnancies and as a result unsafe abortion figures are alarming. Conclusions: By strengthening family planning activities we should fulfill millennium goals referred to sexual and reproductive health services access without discrimination thus reducing even more maternal mortality rates.